Quantitative Analysis of Cenozoic Extension in the Qiongdongnan Basin, South China Sea: Insight on Tectonic Control for Hydrocarbon Reservoir Accumulation and Formation - Yan Zhang; Li Zhang; Lijun Mi; Xiangyang Lu; Shiguo Wu; Lishan Tang; Jie Zhou; Xiaofeng Xiong; Jitian Zhu (Energies, 2022)
Cenozoic extension rates were calculated based on 20 seismic profiles across the Qiongdongnan Basin, South China Sea. The results confirmed that the Cenozoic rifting in the Qiongdongnan Basin exhibited multistage extension and spatiotemporal variation. In terms of the N–S striking seismic profiles, the structural forms of the northern and southern sags of the basin were characterized by narrow half grabens, while the structure at the center sag of the basin was characterized by wide and gentle grabens. The fault strikes in the west of the basin were mainly northeast–southwest trending, whereas those in the east of the basin changed from northeast–southwest trending to nearly east–west trending. The extension rate in the east sag was higher than that in the west area. The extension rate in the middle part was lower relative to the east and west sags. This was because the rifting was controlled by the distribution of the main boundary fault along the basin. Temporally, the Cenozoic extension could be divided into three periods: Eocene, Oligocene, and Miocene. The amount of stretching in the three extension stages was unevenly distributed in the entire basin. The maximum was mainly in the Oligocene Lingshui and Yacheng Formations. The Oligocene extension occurred in the entire basin, and the Eocene extension was limited to the Ledong and Changchang sags. Significant fault activity could be observed during the deposition period of the Yacheng and Lingshui Formations and could be attributed to strong extensional activity. The rifting tectonics controlled the distribution of source rocks and oil-generating window as well as hydrocarbon generation, reservoir formation, and accumulation.